TANTANGAN PEMUKA AGAMA SEBAGAI MEDIATOR ANTARA TRADISI DAN TEKNOLOGI DI DESA DUDA UTARA - Arimbawa, I Komang Suastika; Sari, Anggy Paramitha; Kurniarini, Ni Nyoman Yunike; Pratama, I Gede Bagus Wira (Sanjiwani: Jurnal Filsafat, 2024)
Religious leaders in Desa Duda Utara face challenges in balancing traditional heritage and advancing technology, especially within the context of Society 5.0. This article discusses the role of religious leaders as mediators in efforts to maintain the principle of ataraxia amidst changing times. Based on field observations and interviews, it was found that religious leaders act as bridges between religious traditions and everyday practices, while also serving as figures who uphold social order through guidance and moral advice. However, in facing the modern era with rapid social changes, these leaders often become entrenched in rigid traditional routines. This situation presents a significant challenge, particularly in adapting their teaching methods and leadership to meet the expectations of the younger generation, who prefer more interactive and relevant approaches. Additionally, this study highlights that the lack of technological integration is one of the factors limiting the effectiveness of religious leaders in responding to modern societal needs. Traditional teaching methods now need to be updated by leveraging digital media. It is essential for religious leaders to develop digital literacy skills and adopt more inclusive teaching methods. Collaborating with educational institutions and other organizations is also a strategic step in bridging the gap between traditional teachings and modern dynamics. By making these adaptations, religious leaders in Desa Duda Utara can maintain their central role, strengthen social bonds, and preserve their relevance in an ever-evolving society.